Setting an agenda for biofouling research for the marine renewable energy industry. (September 2017) - Loxton, J.; Macleod, A.K.; Nall, C.R.; McCollin, T.; Machado, I.; Simas, T.; Vance, T.; Kenny, C.; Want, A.; Miller, R.G.
Highlights: Biofouling causes a range of issues for marine renewable energy (MRE) stakeholders. An agenda for biofouling research for the MRE industry is proposed. Biofouling data could reduce operation & maintenance cost and increase efficiency. Site-specific biofouling data could aid the design of MRE devices and components. Current methods of knowledge exchange are insufficient between MRE stakeholders. Abstract: Extensive marine growth on man-made structures in the ocean is commonplace, yet there has been limited discussion about the potential implications of marine growth for the wave and tidal energy industry. In response, the Environmental Interactions of Marine Renewables (EIMR) Biofouling Expert Workshop was convened. Discussions involved participants from the marine renewable energy (MRE) industry, anti-fouling industry, academic institutions and regulatory bodies. The workshop aimed to consider both the benefits and negative effects of biofouling from engineering and ecological perspectives. In order to form an agenda for future research in the area of biofouling and the marine renewable energy industry, 119 topics were generated, categorised and prioritised. Identified areas for future focus fell within four overarching categories: operation and maintenance; structured design and engineering; ecology; and knowledge exchange. It is clear that understanding and minimising biofouling impacts on MRE infrastructure will be vital to the successful development of a reliable and cost effective MRE industry.